MEANINGFUL LIFE VALUES OF THE PERSONALITY IN IVAN OGIENKO'S VIEWS - Марушкевич, Алла (Київський національний університет імені Тараса Шевченка, 2022)
The article proves the importance of Ivan Ohienko-Metropolitan Hilarion's views on the meaning of values of the individual.Examples of his instructions regarding good deeds, ideas about truth, respect for family, parents and relatives have been revealed. The position on the value of people's positive attitude towards prominent figures, heroes of the nation has been highlighted. The scientist's vision of the importance of the native language in the life of each individual, awareness of it as a meaningful life value has been described. The views of the scientist on work for the people, respectful attitude towards it and the work of other people, discipline of the soul, recognition of the achievements of others have been revealed.
СМИСЛОЖИТТЄВІ ЦІННОСТІ ОСОБИСТОСТІ В ПОГЛЯДАХ ІВАНА ОГІЄНКА